Characterization of Students’ Misconseptions Based on Four Tier Diagnostic Test with Certainty of Response Index on Flat Sides 3-Dimensional Figures - Ardiansyah, Novan; Darmawan, Puguh (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
Misconceptions must be detected, one of which is by using the four-tier diagnostic test with certainty of response index. This research aims to examine students' misconceptions based on the confidence level of students' answers and reasons on flat sides 3-dimensional figures. This research is a multi-case study qualitative research. The research subjects consisted of twenty 8th-grade students who experienced misconceptions about the material of sides 3-dimensional figures. The instruments used in this research are the researcher, diagnostic test of flat-sided 3-dimensional figures, and interview guidelines. The data were the subject's written answers and the subject's interview recordings. The research data were analyzed using the classification rubric of the four-tier diagnostic test assessment results with the certainty of response index. The results of this study are the characteristics of four types of classificational misconceptions, four types of correlational misconceptions, and two types of theoretical misconceptions. This study concludes that misconceptions only occur in students who give wrong reasons with a high level of confidence.